Anti-inflammatory activity of Syzygium Cumini leaves - Jain A; Sharma S; Goyal M; Dubey S; Jain S; Sahu J; Sharma A; Kaushik A (International Journal of Phytomedicine, 2010)
The Syzygium cumini (Myrtaceae) is a popular traditional medicinal plant in India. This study was intended to evaluate the antiinflammatory activity of ethyl acetate and methanol extracts of S.cumini leaves in carrageenan induced paw oedema in wistar rats at the dose level of 200 and 400 mg/kg administrated orally. Both the extracts exhibited significant anti-inflammatory activity, which supports the traditional medicinal utilization of the plant. This study established anti-inflammatory activity of leaves of S.cumini.